VD_FINDINFO HC / 2013 / 602 vom 5. September 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, DEMEURE DU DÉBITEUR, RÉSILIATION, EXPULSION DE LOCATAIRE, PROCÉDURE SOMMAIRE | 257d al. 1 CO, 257d al. 2 CO, 86 al. 1 CO, 86 al. 2 CO, 87 al. 1 CO, 7 al. 2 RULV, 257 CPC (CH)